The Effectiveness of Teacher Certification Policy in Addressing the Teacher Crisis in Indonesia - Setiadi, Ade; Muhafidin, Didin (International Journal of Science and Society, 2024)
This study evaluates the effectiveness of teacher certification policy in addressing the teacher shortage crisis in Indonesia. Using a qualitative approach, data were collected from interviews with certified teachers, principals, and policymakers to understand the implementation of the policy, the challenges faced, and its impact on education quality. The results show that although teacher certification can improve pedagogical skills, implementation is often hampered by inadequate operational support, uneven distribution of certified teachers, and budget constraints. Inequitable distribution of teachers, especially in remote areas, as well as budget and ongoing training issues are key issues that reduce the effectiveness of the policy. To increase the impact of the certification policy, better operational support at the school level, incentives for teachers in less developed areas, and most importantly, more effective budget planning are needed. These findings provide important insights for policy makers and education practitioners in designing more comprehensive strategies to improve education quality in Indonesia.